2024
DOI: 10.1007/s00401-024-02695-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells and macrophages as allies in the healthy and diseased brain

Adam Denes,
Cathrin E. Hansen,
Uemit Oezorhan
et al.

Abstract: Diseases of the central nervous system (CNS) are often associated with vascular disturbances or inflammation and frequently both. Consequently, endothelial cells and macrophages are key cellular players that mediate pathology in many CNS diseases. Macrophages in the brain consist of the CNS-associated macrophages (CAMs) [also referred to as border-associated macrophages (BAMs)] and microglia, both of which are close neighbours or even form direct contacts with endothelial cells in microvessels. Recent progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…Moreover, the same study showed that neutrophils preferentially extravasate into the circumscribed locations adjacent to PVMs. In our case, PVMs are in an ideal anatomical position to contribute to focal chemokine gradients [ 8 , 9 ], which may either be transported to the luminal surface of endothelial cells and/or act as a migratory signal for peripheral immune cells. Data from isolated CAMs in naïve conditions revealed their ability to produce different chemoattractants under physiological conditions, including different interleukins and chemokines [ 18 ] involved in neutrophil recruitment [ 14 , 30 , 32 , 34 , 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the same study showed that neutrophils preferentially extravasate into the circumscribed locations adjacent to PVMs. In our case, PVMs are in an ideal anatomical position to contribute to focal chemokine gradients [ 8 , 9 ], which may either be transported to the luminal surface of endothelial cells and/or act as a migratory signal for peripheral immune cells. Data from isolated CAMs in naïve conditions revealed their ability to produce different chemoattractants under physiological conditions, including different interleukins and chemokines [ 18 ] involved in neutrophil recruitment [ 14 , 30 , 32 , 34 , 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAMs are a distinct population of brain resident macrophages located within CNS interfaces, which include the perivascular spaces (perivascular macrophages, PVMs), the leptomeninges (meningeal macrophages, MMs), and the choroid plexus (choroid plexus macrophages, ChPM) and are identified in human and mouse brain as CD163 + and CD206 + cells, respectively [ 12 ]. Recent studies have indicated that CAMs are involved in a wide variety of pathological states [ 8 , 9 , 23 , 48 ]. Their main functions, as described to date, include regulation of blood–brain barrier (BBB) integrity and cerebrospinal fluid (CSF) dynamics, phagocytosis of blood-borne pathogens, and control of leukocyte migration [ 10 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This specific relation may be attributed to direct cell-to-cell contact, secretion of cytokines, chemokines, growth factors, or exosomal vesicles. It is known that EPCs’ relation with macrophages in the brain plays a critical role in regulating blood–brain barrier function, vascular perfusion, and inflammation [ 105 ]. Similar close relations exist in the maintenance of muscular biology/regeneration and bone homeostasis [ 106 , 107 , 108 ].…”
Section: Future Perspectivesmentioning
confidence: 99%